Design of a single screw extruder machine for 3d printing filament production application - Maulana, Achmad Bagas; Widodo, Edi; Fahruddin, Arasy; Yulianto, Sulis (Universitas Muhammadiyah Jakarta, 2023)
This study aims to determine the optimal 3D Printer filament extruder machine design, to determine the design of the extruder components for filament production, to determine the single screw design used for filament production. The research method used is creating flow chart, the result of the research is the calculation of the diameter of the 3D Printer filament of 1.77 mm, by measuring the diameter of the filament by taking a 2 meters long sample to be measured every 10 cm. the most influential components in this research are diameter, length of single screw extruder, length of filament winding process, production capacity and total electric power. With a screw speed of 5 RPM, 1.5 kg of ready-to-use 3D printer filament is produced within 1 hour of production. So there, is an error between the calculation and the real condition of 15%.